2023
DOI: 10.3390/cryst13020229
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Excellent Enhanced Photocatalytic Degradation of Methylene Blue Using Silver-Doped Zinc Oxide Submicron Structures under Blue Laser Irradiation

Abstract: In this study, laser-assisted chemical bath synthesis (LACBS) was used to prepare pure and Ag-doped ZnO submicron structures using a simplified hydrothermal approach that did not require a catalyst. The photocatalytic degradation of Methylene Blue was investigated under blue laser irradiation (λ = 444.5 nm and I = 8000 lx). The doping concentration varied (2%, 4%, 6%, 8%, tando 10%) and was prepared by LACBS using a continuous blue laser (P = 7 W, λ = 444.5 nm) for the first time. XRD, FE-SEM, EDX, and UV-Vis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The peaks of TZ and TZC at 393 nm are stronger than the others compared with T0 and TC, indicating the presence of ZnO. The UV luminescence peak of ZnO is at around 391 nm [66]. A shoulder appears at 423 nm in the ZC and ZTC samples, which may belong to the effect produced by the C entry into the lattice.…”
Section: Resultsmentioning
confidence: 89%
“…The peaks of TZ and TZC at 393 nm are stronger than the others compared with T0 and TC, indicating the presence of ZnO. The UV luminescence peak of ZnO is at around 391 nm [66]. A shoulder appears at 423 nm in the ZC and ZTC samples, which may belong to the effect produced by the C entry into the lattice.…”
Section: Resultsmentioning
confidence: 89%
“…where k is the constant (k= 0.9), θ is the Bragg diffraction angle, λ is the X-ray source wavelength (λ = 1.5427), and β is FWHM. The lattice constants (a, b, and c) of the doped and undoped ZnO were calculated using Bragg's law [33]:…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…The degradation of organic dyes using photocatalysis is highly dependent on the generation of electron-hole pairs, which requires semiconductor catalysts to absorb more light efficiently. To achieve this, doping ZnO with Ni-significantly enhances the former's photocatalytic characteristics by extending the lifespan of the electron-hole pairs and increasing the compound's light-harvesting capacity [33]. The process involves exposing the ZnO nanostructure to blue laser photons, which could excite electrons from the valence band to the conduction band, creating holes in the valence band.…”
Section: Photocatalytic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Abdullah et al [32] synthesized a ternary CuO/CuS/MnO 2 nanocomposite that showed 98% MB degradation under visible light irradiation in 160 min. Zyoud et al [33] synthesized a 10% Ag-doped ZnO catalyst and achieved higher MB photodegradation at 444.5 nm irradiation as compared to ZnO. Zhao et al [34] synthesized ZnO nanoflower arrays (ZnO NFAs), in which the ZnO nanorods were grown vertically downward and formed ZnO NFAs.…”
Section: Introductionmentioning
confidence: 99%